17. Somatosensory evoked potentials recorded during hypothermia in neonatal hypoxic–ischemic encephalopathy. Issue 1 (January 2015) - Agatiello, M.; Toffoli, E.; Scarabel, F.; Tessari, L.; Traverso, A.; Bizzaro, E.; Capua, M. Di; Pro, S.; Cappellari, A.; Suppiej, A.
<x xml:space="preserve">Abstract</x> Bilateral loss of N20 predicts cerebral palsy in neonatal hypoxic ischemic encephalopathy (Suppiej, 2010). The diffusion, in the last years, of the hypothermic treatment in this condition, requires to reevaluate their prognostic role and timing of SEPs. Aim of this study is to evaluate the most appropriate timing during which to perform the evoked potentials. Twelve newborns underwent median nerve SEPs during hypothermia (33.5 °C), and subsequently between the 5th and the 14th day of life. Of the 12 newborns studied the N20 was bilaterally absent during hypothermia in 6, but bilaterally present in normothermia in 4, the remaining 2 died before the control SEP. Only in 1/12 the N20 was bilaterally recorded during hypothermia. In 3cases the N20 was absent unilaterally, in 2/3 was subsequently recorded bilaterally while in 1/3 persisted unilaterally absent; this neonate had an ipsilateral stroke. Since bilateral absence of cortical SEPs performed at the end of the first week of life was shown to predict cerebral palsy later in life, the discrepancy between the SEPs recorded during hypothermia and the SEPs recorded once normothermia has been attained, suggest a low prognostic value of SEPs recorded during hypothermia, differently from adults (Zanatta, 2012).